Analisa Penerapan Key Performance Indicator Untuk Peningkatan Kualitas Performa dan Budaya HSSE Pada Sektor Industri Hulu Minyak Dan Gas (Studi Kasus: Fungsi Hsse Pt. Xyz) - Palayukan, Arthur Gamara; Hasibuan, Bernard; Ramli, Soehatman; Sugiarto, Sugiarto (Syntax Corporation, 2025)
Health, Safety, Security, and Environment (HSSE) are fundamental aspects in the high-risk upstream oil and gas industry. This study aims to develop Key Performance Indicators (KPIs) that effectively represent the quality of HSSE management system implementation while also strengthening HSSE culture within organizations. Utilizing a quantitative approach through questionnaire distribution to workers in the oil and gas sector, this research analyzes the influence of various variables such as leadership, reporting systems, training, employee engagement, as well as indicator characteristics like collegial and initiative-based indicators on the effectiveness of HSSE KPIs. A conceptual model was developed and tested using descriptive and quantitative analysis. The findings reveal that management system of performance, HSSE management system and budget management does have a significant impact on the successful implementation of HSSE KPIs, which directly contributes to the strengthening of workplace HSSE culture. The study also proposes a tiered performance measurement framework that is more adaptive in supporting data-driven decision-making in HSSE risk management. The outcomes of this study are expected to provide practical contributions in developing KPIs that are not only quantitative but also reflective of safety culture values. Furthermore, it serves as a reference for designing more holistic and sustainable HSSE policies.